On the genus Typhlopolycystis Karling, 1956 (Platyhelminthes, Kalyptorhynchia, Polycystididae), with data on the five known species and the description of eleven new species - Schockaert, Ernest R.; Moons, Patricia; Janssen, Toon; Tessens, Bart S.; Reygel, Patrick C.; Revis, Nathalie; Jouk, Philippe E. H.; Willems, Wim R.; Artois, Tom J. (Zootaxa, 2019)
An overview is given of all representatives of the genus Typhlopolycystis Karling, 1956: the five known species (T. coeca Karling, 1956; T. mediterranea Brunet, 1965; T. coomansi Schockaert and Karling, 1975; T. schockaerti Karling, 1978 and T. rubra Noldt and Reise, 1985) and eleven new species: T. microphthalma n. sp. from S. France, T. fonsecai n. sp. and T. maikoni n. sp. from Brazil, T. norenburgi n. sp. and T. leasiae n.sp from the Pacific coast of Panama, T. pluvialiae n. sp. from Lanzarote (Canary Islands, Spain), T. riegeri n. sp. from Tanzania, T. tahitienis n. sp. from French Polynesia, T. australiensis n. sp. from South Australia, T. sarda n. sp. from Sardinia (Italy), the S. of France and from Lanzarote, and T. errata n. sp. from Sardinia (Italy). We consider T. limicola Schilke, 1970 as a species inquirenda of which no type material exists. Finally, some comments are given on the distribution of the genus of which representatives have been found in almost all places that have been sampled world wide.